Preface / Ts. Jamal Othman - Othman, Jamal (Unit Penerbitan JSKM, 2023)
The committee of SIG CS@e-Learning would like to convey our sincere gratefulness to Almighty for the fifth issue contributed by educators from the Kolej Pengajian Pengkomputeran, Informatik dan Media (KPPIM), UiTM Penang Branch. Total of 18 academic articles have been received by the committee and all papers were accepted. The articles submitted shown that the contents and research framework discussed are adequate and the authors are recommended to enhance the paper by adding part of findings and discussions to be published in journals with SCOPUS, WOS or ERA indexed. The theme of fifth volume is focusing on Enhancing Innovations in e-Learning for Future Preparation. E-learning has become an increasingly important learning and teaching mode in recent decades and has been recognized as an efficient and effective learning method. The rapidly rising number of Internet users with smartphones and tablets around the world has supported the spread of e-learning, not only in higher education and vocational training but also in primary and secondary schools. New trends in e-learning will be covered under artificial intelligence (AI), micro credentials, big data, virtual and empowered reality, blended learning, cloud e-learning, gamification, mobile learning, Internet of things, and online video.